ANALISIS YURIDIS TERHADAP PENETAPAN HAK ASUH ANAK DALAM KASUS PERCERAIAN DI PENGADILAN AGAMA KABUPATEN CIREBON: A. KASUS PERCERAIAN DI KABUPATEN CIREBON, B. JAMINAN KEPASTIAN HAK ASUH ANAK PADA KASUS PERCERAIAN DI KABUPATEN CIREBON - Agni, Mohammad Agni Ariyanto; Kosim; Abdul Aziz; Ahmad Khalimy (Jurnal Studi Islam, 2025)
Abstract: In a study conducted by Umul Khair, it was found that the implementation of child custody after divorce is not always in accordance with the decision taken by the religious court. Especially related to the fulfillment of child support rights, this is not only a legal obligation for parents, but also an implementation of the purpose of marriage in Islam, namely to protect offspring. By providing basic needs such as housing, clothing, food, medical expenses, and education, parents make a significant contribution to the optimal growth and development of children. This article has two significant objectives. First, to find out about divorce cases in Cirebon Regency and Second, to find out the guarantee of certainty of child custody rights in divorce cases in Cirebon Regency. The method used in this study is a qualitative method with a descriptive approach. The results of the study show that child custody is often given to a mother, in accordance with legal provisions. However, in its implementation, it faces various obstacles, especially in terms of fulfilling child support obligations by the father. Many ex-husbands do not carry out their responsibilities, thus increasing the burden on the mother as the main caregiver. In addition, the strained relationship between ex-husbands often hinders communication and cooperation in child care. Keywords: Certainty, Guarantee, Child Custody.